Development of the procedure of quantitative determination of the biological active substances in the extract of a bupleurum aureum in the composition of a combined dosage form - Glushchenko, Alla; Bezruk, Ivan; Bevz, Nataliia; Ivanauskas, Liudas; Georgiyants, Victoriya (ScienceRise: Pharmaceutical Science, 2019)
Nowadays, combined medicines are becoming more and more widespread. The combination of active pharmaceutical ingredients is necessary to increase the therapeutic effect or shorten the treatment period, or prevent possible complications. The aim of the work is to develop a method for the quantitative determination of biologically active compounds of dry extract of Bupleurum aureum as part of a combined dosage form in the form of a syrup in a mixture with loratadine. Methods. Identification of flavonoids in the extract was carried out by HPLC. To determine the quantitative content of flavonoid substances, the method of absorption spectrophotometry in the visible spectral range was used, based on the formation of colored complexes of flavonoids with a solution of aluminum chloride in an acidic medium. Results of the research. As a result of the research, a spectrophotometric method was developed to quantify the amount of flavonoids in the combined syrup with loratadine and Bupleurum aureum dry extract. The HPLC method establishes the flavonoids contained in the extract. The resulting colored complexes of alcoholic extracts from the syrup after the reaction of interaction with a solution of aluminum chloride in an acetic acid medium were characterized by the presence of absorption maxima at a wavelength of 412 nm. The effect of background absorption is insignificant noise δ = 0.25 %, max δ = 0.51 %. The studied validation characteristics of the technique, which indicate a linear dependence of the amount of flavonoids in terms of rutin in the range of concentration of Bupleurum aureum extract in syrup from 80 % to 120 %, since the value of the correlation coefficient (r) is 0.9999 ³ 0.9981; the angular coefficient of the linear dependence (b) is 0.9947, the free term of the linear dependence (a) is 0.52 £ 1.60. The technique is precise, since the value of the relative confidence interval is less than the critical value for the convergence of the results: D % = 0.37 ≤ 2.60 and the criterion of insignificance of systematic error is fulfilled d = 0.01. Conclusions. The HPLC method established the presence in the dry extract of the aerial part of the Bupleurum aureum substance of the flavonoid structure, which became a prerequisite for the standardization of the active substance in the syrup in the sum of these biologically active compounds. A spectrophotometric method of quantitative determination in the visible region of the sum of flavonoids in terms of rutin in the combined dosage form in the form of a syrup in the presence of another active ingredient loratadine has been developed